Development of an LFD-RPA Assay for Rapid Detection of Pentatrichomonas hominis Infection in Dogs - Yao Rong; Xichen Zhang; Xuejiao Chen; Jianhua Li; Pengtao Gong; Xiaocen Wang; Xin Li; Xu Zhang; Taotao Yue; Hongbo Zhang; Xiaofei Zhou; Nan Zhang (Current Issues in Molecular Biology, 2023)
Pentatrichomonas hominis is a trichomonad protozoan that infects the cecum and colon of humans and other mammals. It is a zoonotic pathogen that causes diarrhea in both animals and humans. As companion animals, dogs infected with P. hominis pose a risk of transmitting it to humans. Current methods, such as direct smears and polymerase chain reaction (PCR), used for P. hominis detection have limitations, including low detection rates and the need for specialized equipment. Therefore, there is an urgent need to develop rapid, sensitive, and simple detection methods for clinical application. Recombinase polymerase amplification (RPA) has emerged as a technology for rapid pathogen detection. In this study, we developed a lateral flow dipstick (LFD)-RPA method based on the highly conserved SPO11-1 gene for detecting P. hominis infection by optimizing the primers, probes, and reaction conditions, and evaluating cross-reactivity with genomes of Giardia duodenalis and other parasites. The LFD-RPA method was then used to test 128 dog fecal samples collected from Changchun. The results confirmed the high specificity of the method with no cross-reactivity with the five other parasites. The lowest detection limit of the method was 102 copies/µL, and its sensitivity was 100 times higher than that of the conventional PCR method. Consistent with the positivity rate observed using nested PCR, 12 samples (out of 128) tested positive using this method (positivity rate, 9.38%). In conclusion, the LFD-RPA method developed in this study represents a simple and sensitive assay that allows for the rapid detection of P. hominis infection in dogs, especially in this field.